Afta : location decision in the timber of Sarawak & Kalimantan - Buttar, Dharshan Singh (Universiti Malaysia Sarawak (UNIMAS), 2002)
As timber is the main industry within this area, this research will study the impact of Afta on the relocation of firms from the high cost of production in Sarawak to the low cost areas in Kalimantan.